Revisiting the attempts to fortify methionine content in plant seeds. (26th March 2019) - Amir, Rachel; Cohen, Hagai; Hacham, Yael
Abstract : We describe diverse genetic and molecular approaches used to increase methionine content in seeds, and discuss the biotechnological potential of these manipulations.  Abstract: The sulfur-containing amino acid methionine belongs to the group of essential amino acids, meaning that humans and animals must consume it in their diets. However, plant seeds have low levels of methionine, limiting their nutritional potential. For this reason, efforts have been made over the years to increase methionine levels in seeds. Here, we summarize these efforts and focus particularly on those utilizing diverse genetic and molecular tools. Four main approaches are described: (i) expression of methionine-rich storage proteins in a seed-specific manner to incorporate more soluble methionine into the protein fraction; (ii) reduction of methionine-poor storage proteins inside the seeds to reinforce the accumulation of methionine-rich proteins; (iii) silencing methionine catabolic enzymes; and (iv) up-regulation of key biosynthetic enzymes participating in methionine synthesis. We focus on the biosynthetic genes that operate de novo in seeds and that belong to the sulfur assimilation and aspartate family pathways, as well as genes from the methionine-specific pathway. We also include those enzymes that operate in non-seed tissues that contribute to the accumulation of methionine in seeds, such as S -methylmethionine enzymes. Finally, we discuss the biotechnological potential of these manipulations to increase methionine content in plant seeds and their effect on seed germination.